IMPLEMENTASI PEMBELAJARAN BERBASIS ERA DIGITAL TERHADAP PENDIDIKAN KARAKTER DI SD MUHAMMADIYAH PANGKALPINANG - Mubarok, Arian Rizqon; Martaningsih, Sri Tutur; Hidayati, Dian (Jurnal Kepemimpinan dan Pengurusan Sekolah, 2025)
The purpose of this study is to describe: 1) Implementation of Digital Era-Based Learning on Character Education in SD Muhammadiyah Pangkalpinang 2) Supporting and inhibiting factors of Digital Era-Based Learning on Character Education in SD Muhammadiyah Pangkalpinang. This type of research uses descriptive qualitative research. The subjects in this study include: Teachers, as online learning teachers and students as online learning targets. Data collection techniques using interviews and documentation. The techniques used in data analysis are data reduction, data presentation, and drawing conclusions. The results of the study are as follows: 1) The implementation of Digital Era-Based Learning on Character Education in SD Muhammadiyah Pangkalpinang through 3 stages, namely the planning, implementation, and evaluation stages. Planning includes: online learning methods, and the suitability of online learning materials. Implementation includes: online learning process, online learning time and schedule, online student participation, and online learning media. Evaluation includes: Online Learning Assessment, and Online Learning Constraints. 2) Supporting and inhibiting factors of Digital Era-Based Learning on Character Education at SD Muhammadiyah Pangkalpinang.